Penerapan Sistem Ekonomi Kerakyatan Berbasis Ekonomi Digital dalam Membangkitkan Kenaikan Pendapatan Pada UMKM: Studi Kasus Pada UMKM Kuliner di Desa Margasari, Kab. Karawang - Dhea Imroatul Fatihah; Trias Arimurti; Futri Amirotud Dzakiah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Capital ownership among Indonesian people is encouraged by the People's Economic System which is based on justice, democracy and kinship. Indicators of the implementation of the Community Economic system in Indonesia include Micro, Small and Medium Enterprises (UMKM), most of which are owned by regional communities through capital. To increase the income of MSMEs in Indonesia, the aim of the study is to implement a digital economy-based community economic system. The findings of this research indicate that MSMEs in Margasari Village, Kab. Karawang, can increase its income by implementing a digital economy-based community economic system. Observation, interviews, questionnaires and documentation are tools used to obtain data for a qualitative descriptive research approach.